Hispanic Caregivers' experience of pediatric type 1 diabetes: A qualitative study. Issue 7 (21st July 2021) - Tremblay, Elise Schlissel; Ruiz, Jessica; Dykeman, Blair; Maldonado, Michele; Garvey, Katharine
Abstract: Objective: It is widely recognized that Type 1 Diabetes (T1D) outcomes are worse among Hispanic children; however, little is published about the perspectives of these patients and their caregivers. Our intent was to characterize the lived experience of Hispanic caregivers of children with T1D, focusing on the role of language and culture and their perspectives on current medical care and alternative care models. We studied Hispanic caregivers of patients (age 2–17 years) with T1D of greater than 6 months' duration. Research Design and Methods: We completed semi‐structured interviews and focus‐groups of a purposive sample of 20 members of our population of interest. We developed a codebook and completed multidisciplinary consensus coding, then conducted iterative thematic analysis using qualitative software and discussion to generate themes. Results: We gathered data from 20 Hispanic caregivers of T1D patients (11.37 ± 3.00 years old, 4.80 ± 2.84 years since diagnosis). 85% of caregivers were female, 80% preferred Spanish, and 15% were college‐educated. Our analysis yielded 4 themes across the participants: (1) Culturally‐based nutrition challenges, (2) Social isolation and lack of support for T1D care, (3) Hesitancy to fully embrace diabetes technology, and (4) Deferential views of care experience and providers. Overarching all of these themes was support for Hispanic group‐based models of care tailored to address these concerns. Conclusions: The unique concerns among Hispanic caregivers of children with T1D suggest the importance of culturally tailored interventions to improve care. With successful implementation, such interventions could diminish widening disparities in healthcare outcomes.